возведем обе части в квадрат
тогда по теореме Виета
![image](https://tex.z-dn.net/?f=x_%7B1%7D%2Bx_%7B2%7D%3D10%5C%5C%0Ax_%7B1%7Dx_%7B2%7D%3D24-a%5E4-2a%5E2%5C%5C%5C%5C%0A1%2924-a%5E4-2a%5E2%3E0%5C%5C%0A2%2924-a%5E4-2a%5E2%3C0%5C%5C%5C%5C%0Aa%5E2%3Dt%5C%5C%0A1%29-t%5E2-2t%2B24%3E0%5C%5C%0A+D%3D4%2B4%2A1%2A24%3D10%5E2%5C%5C%0A+t%3D-6%5C%5C%0A+t%3D4%5C%5C%0A+a%3D2%3B-2%5C%5C%0A+%28-2%3B2%29+%5C%5C%5C%5C%0A)
0\\
2)24-a^4-2a^2<0\\\\
a^2=t\\
1)-t^2-2t+24>0\\
D=4+4*1*24=10^2\\
t=-6\\
t=4\\
a=2;-2\\
(-2;2) \\\\
" alt="x_{1}+x_{2}=10\\
x_{1}x_{2}=24-a^4-2a^2\\\\
1)24-a^4-2a^2>0\\
2)24-a^4-2a^2<0\\\\
a^2=t\\
1)-t^2-2t+24>0\\
D=4+4*1*24=10^2\\
t=-6\\
t=4\\
a=2;-2\\
(-2;2) \\\\
" align="absmiddle" class="latex-formula">
Ответ при